Hubungan Gaya Belajar Dengan Multiple Intellegences Terhadap Prestasi Peserta Didik - Sufianti, Alif Via (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is based on the importance of understanding students' learning styles to improve students' academic. The purpose of this study is to find out and understand the relationship between learning styles and multiple intelligences, the achievement of students at MI Muhammadiyah Banjarsari. The method used in this research is through library research contained in various books, papers, and various other sources. Data sources in this study were students at MI Muhammadiyah Banjarsari. Journal analysis and regarding the relationship between learning styles and multiple intelligences show that students' learning styles in capturing information have a close relationship with the multiple intelligences possessed by each student, resulting in academic achievement based on students.